Co-delivery of hydrophilic gemcitabine and hydrophobic paclitaxel into novel polymeric micelles for cancer treatment. Issue 39 (3rd May 2017) - Di, Yan; Gao, Yunyun; Gai, Xiumei; Wang, Dun; Wang, Yingying; Yang, Xiaoguang; Zhang, Dan; Pan, Weisan; Yang, Xinggang
Abstract : Schematic illustration of the preparation and intracellular performance of GEM–VE and PTX–VE loaded FA–PEG–VE micelle. Abstract : This study was carried out to investigate an effective method for the co-delivery of Gemcitabine (GEM) and paclitaxel (PTX) into tumor cells. GEM and PTX were modified with functional (+)-α-tocopherol (VE) to obtain similar water solubility. Folic acid-poly(ethylene glycol)–(+)-α-tocopherol (FA–PEG–VE) was designed to co-encapsulate the modified GEM and PTX. Methoxy poly(ethylene glycol)–poly(lactide- co -glycolide) (MPEG–PLGA) was used as a control. The characterizations of micelles were examined by DLS and TEM. It was found that two drugs-loaded FA–PEG–VE micelles, (GPF) and MPEG–PLGA micelles (GPM), had a spherical morphology with an average diameter of 127 nm and 118.9 nm, respectively. GEM–VE and PTX–VE encapsulation efficiencies of GPF were 91.09 ± 0.03%, 92.46 ± 0.02% (88.60 ± 0.03%, 89.32 ± 0.04% of GPM). In vitro release of GPF, 2.73% of GEM–VE and 2.88% of PTX–VE, were accumulatively released in 72 h (4.04% of GEM–VE and 3.88% of PTX–VE from GPM). Furthermore, comparisons of cytotoxicity were made with different fomulations. The IC50 of GPF after 72 h incubation was lowest. FA–PEG–VE micelle showed higher uptake efficiency than that of MPEG–PLGA micelle. Clathrin-mediated and energy-dependent endocytosis was involved in uptake mechanisms. These results demonstrated that GEM–VE and PTX–VE loaded FA–PEG–VE micelles would be a potentially useful prodrug-based nano-drug delivery system for cancer treatment.